EVALUATION OF PRESSURE DATA NOISE EFFECT IN OOIP AND DRIVING MECHANISM DETERMINATION USING MATERIAL BALANCE - (NIM: 22208045); Pembimbing : Dr. Ir. Taufan Marhaendrajana, RAMADHANIA
Pressure data are important factor to get the accurate result in material balance calculation. In fact, there are difficulties to reach actual static reservoir pressure, so that it results noise in pressure data and we have to estimate the pressure values. Therefore, this research will evaluate effect of that kind of estimation in OOIP and driving mechanism determination using material balance calculation. This research contains two main parts. First part is consistency test of OOIP calculation between straight line method, regression method, and sensitivity analysis. Second part is evaluation of effect of noisy pressure data in OOIP and driving mechanism determination using three kinds of methods. Results of this research point out that straight line method, regression method, and sensitivity analysis yield consistency OOIP calculation and different pressure data estimation yield different results of OOIP and driving mechanism determination using those methods.